2022
DOI: 10.2337/dc23-s005
|View full text |Cite
|
Sign up to set email alerts
|

5. Facilitating Positive Health Behaviors and Well-being to Improve Health Outcomes:Standards of Care in Diabetes—2023

Abstract: The American Diabetes Association (ADA) “Standards of Care in Diabetes” includes the ADA’s current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee, are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed description of ADA standards, statements, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
204
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(215 citation statements)
references
References 441 publications
6
204
0
5
Order By: Relevance
“…Of note, we observed that BMI, fasting insulin, and type 2 diabetes seemed to partly mediate the associations of LST and MVPA with gastrointestinal diseases, which indicates that metabolic factors may involve in the pathological process. In addition, given that a comparative proportion of the effect was mediated by type 2 diabetes, our results support the current guidelines that recommend increasing activity and decreasing sedentary behavior among type 2 diabetes patients from the American Diabetes Association to improve their overall well-being (38). Similarly, more physical exercise and less sedentary time should also be recommended among obese individuals as a part of the management of gastrointestinal health due to the mediation effects of BMI observed in the link from physical activity and sedentary lifestyle to gastrointestinal disease in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Of note, we observed that BMI, fasting insulin, and type 2 diabetes seemed to partly mediate the associations of LST and MVPA with gastrointestinal diseases, which indicates that metabolic factors may involve in the pathological process. In addition, given that a comparative proportion of the effect was mediated by type 2 diabetes, our results support the current guidelines that recommend increasing activity and decreasing sedentary behavior among type 2 diabetes patients from the American Diabetes Association to improve their overall well-being (38). Similarly, more physical exercise and less sedentary time should also be recommended among obese individuals as a part of the management of gastrointestinal health due to the mediation effects of BMI observed in the link from physical activity and sedentary lifestyle to gastrointestinal disease in this study.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, these ingredients have been implied to offer glycemic benefits [36,37,[39][40][41][42][43]61] which may offer additivity with the MLE, although some of the effects of particular blend ingredients for glucose benefits have been debated [62][63][64], in particular low-dose vitamin D 3 . Thus, this mix can provide added nutritional value to people with T2D, thus supporting long-term adherence, which is also supported by recent guidelines [65] that now advocate a ''patient-centered approach,'' where, for many people with T2D, nutritional supplements, if supported by evidence, tend to be desired over adding another medication.…”
Section: Discussionmentioning
confidence: 77%
“…This strongly suggests that the noted improvements in glycemic control, diastolic blood pressure, lipids, and body weight were due to lifestyle changes themselves, rather than to increases in medications. Typically, healthy lifestyle behaviors are synergistic with medications, resulting in clinical improvements and lower cardiometabolic risk without higher medication burden ( 21–25 ). In some cases lifestyle changes may allow for the reduction or cessation of medication.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other lifestyle behaviors including regular physical activity, restorative sleep, and stress management are associated with positive health outcomes ( 18–20 ). Leading medical organizations including the American Diabetes Association ( 21 ), American Association of Clinical Endocrinology ( 22 ), American College of Cardiology ( 23 ), American Heart Association ( 24 ), American Society for Preventive Cardiology ( 25 ), National Lipid Association ( 26 ), and the American Cancer Society ( 27 ) all recommend lifestyle change, including plant-predominant eating patterns, as first-line therapy.…”
Section: Introductionmentioning
confidence: 99%